A generation caught between two eras - The drastic shift from communism to capitalism in Albania. - Bruçi, Elvira (European Journal of Sustainable Development, 2016)
The year 1945 marks the beginning of the darkest era in the history of the Albanian people. At a time where Europe had just come out of the Second World War, in a state of huge destruction and grief, with little attention towards the smaller states, communism was established in Albania, followed by unprecedented violence, unconstitutional trials, deportations, persecutions, overall paranoia and a nationalist hysteria. Enver Hoxha became the undisputable political and social leader of the country, implementing a doctrine of aggression, national isolation and espionage. The economy switched from private to state collective, so the people were expropriated. The elite of the society, which was a threat to the new regime, were mostly persecuted, after being put though ridiculous trials, or even without being trialed, many were jailed, executed or tortured to death. The long period of Enver Hoxha’s governing, (1945-1985), was marked by a massive manipulation of people’s minds and fates. People lived in terror and under a continuous pressure of espionage from the state security. The regime built a doctrine of "biography", according to which people were judged by origins and the fates of many were settled or cursed by a rebellious father, brother, or even distant relative. It would take the death of a dictator (Hoxha), and a massive popular rebellion, protests and the rise of the students in demonstrations, for the trigger of the first state negotiations. The aim of this work is to bring to light once again, the struggle of the Albanian people through the dictatorship and also those following the fall of it. The remarkable influence of this era and the beginning of democracy, the huge gap between the ideologies and the attempts of the people to adapt to the new regime. Key words: communism, terror, espionage, isolation, persecution, capitalism.